Web-based device workflow management engine - Ngeow, Y. C.; Chieng, D.; Mustapha, A. K.; Goh, E.; Low, H. K. (IEEE, 2007)
We present a novel Web-based Device Workflow Management Engine (WDWME) that supports seamless control and coordination of hardware devices. With this workflow engine, a series of activities or workflows regarding hardware functionality or services can be rapidly created via drag and drop. A working web-based workflow prototype has been developed as a proof of concept and tested using a device simulator to capture the task executions. In this work, a Feature Interaction Detection Engine (FIDE) is employed to validate the possible operation conflicts during the creation and pre-execution of a workflow. Additional Justified-Event- Condition-Action (JECA) rule and a Case-Based Reasoning (CBR) are proposed as future work to enhance the system's exception handling capability.